Ponderal Substitutent Effect on the Solubility of an Octahedral Metal Complexes and its Quantative Correletion - Jessy, J.M. (Asian Journal of Chemistry, 2010)
Solubilities of the cobalt(III) complex, CO[(NH3)5Cl]CI2 were determined in alcohol-water mixtures of lower aliphatic alcohols. The solubility was found to decrease steadily with increasing alkyl substitution in the alcohol. This is attributed to the ponderal effect of the alkyl groups. As expected for ponderal effect, the logarithm of relative solubilities determined by two different methods gives good linear correlation with log (1/μ) where 'μ' is the reduced molecular weight of solvent and solute.